ANALISIS EFISIENSI PRODUKSI PERTANIAN SAYURAN DI KOTA DUMAI - Algi Variski; Djaimi Bakce; Evy Maharani (Indonesian Journal of Agricultural Economics, 2021)
Dumai city has excellent potential in agriculture sector. Vegetables production in Dumai City in the last five years has fluctuated. The common problems faced by vegetable farmers in Dumai City are pests and diseases, floods, and land tenure. The objective of this study is to analyze the efficiency of vegetables production in Dumai City. Data Envelopment Analysis (DEA) which is nonparametric method based on linear programming was used to answer the objective of this study. The main findings of this study indicate: firstly, most vegetable farming has been technically efficient, this is because the farming cultivation techniques done by the farmers are in accordance with its purpose. Secondly, most vegetable farming in Dumai City is inefficiently allocative, this is because the excessive use of input, especially in the use of organic fertilizers, and the high ratio of input prices to output prices which is also the cause of allocative inefficiency. Thirdly, vegetable farming in Dumai City is mostly inefficient economically. The government should develop local specific cultivation techniques because the cultivation technique used by farmers is still equivalent to the provincial level, there is no local specific cultivation technique. Besides that, it is necessary to control the increases of input price and the increases of the vegetable selling price that affect to the increases of farmers’ income.